Incidence rate and burden of illness at the Pyeongchang 2018 Paralympic Winter Games - Derman, W.; Runciman, P.; Jordaan, E.; Schwellnus, M.; Blauwet, C.; Webborn, N.; Lexell, J.; van de Vliet, P.; Kissick, J.; Stomphorst, J.; Lee, J. H.; Kim, K. S. (British Journal of Sports Medicine, 2019)
Objective: To describe the incidence rate (IR) and illness burden (IB) at the Pyeongchang 2018 Paralympic Winter Games.